Comportamento morfológico e sedimentológico do litoral de Itaipuaçú (Maricá) e Piratininga (Niterói), RJ, nas últimas três décadas - Silva, André Luiz Carvalho da (2006)
This study was carried on in the Itaipuaçú and Piratininga beaches (Rio de Janeiro state) with the main objective of understanding the morphological and sedimentological behavior of this coastal region along the last three decades. Data was obtained through the following procedures: (1) new beach topographic profiles with concomitant sampling of surface sediments; (2) mapping the sand barrier crest and washover fans with DGPS; (3) analysis of the aero photographies and satellite images; (4) comparing new data to dataset published by several authors between the decades of 1970 and 2003. The results show that the Itaipuaçú beach presents very dynamic profiles at the west sector; this dynamic decreases gradually toward the east, because the greater vulnerability of this area to southwest storm waves. The beach sediments are very coarse sand and pebbles in the west sector and bettersorted coarse sand toward the east. The mapping of the sand barrier crest and washover fans present to the west of the sandy barrier in Itaipuaçú revealed that the barrier has retreated 13 meters during the last 28 years. However, when recent beach topographic profiles are compared to profiles collected in the 70 s no beach erosive behavior is observed: the profiles show the same beach width. In Piratininga, the beach at the west sector also shows highly dynamic profiles as the result of south-west storm wave action. Nevertheless, the beach as a whole presents significant variation in width. The partial destruction of the sidewalk along the beach indicates the strong action of storm waves, further increased by the effect of the wave upon the sidewalk. The beach sands in Piratininga are medium improving sorting towards the east. As observed in Itaipuaçú, the comparison between recent beach profiles with those obtained in the 70 s do not indicate beach erosion: the width of the beach arc center has remained the same along the last three decades.